Effect of ultrasonic-electric surface modification on metal material. (April 2020) - Liu, D; Zhao, J Z; Gao, Y; Liu, J B; Shen, Y L; Meng, C
Abstract: With the demand for the materials are increasing in the field of military and civilian application with each passing day, an ultrasonic-electric surface modification treatment was employed to improve the surface properties of metal material with different heat-treated conditions. The surface properties of the specimens after conventional cutting and ultrasonic-electric surface modification treatment were characterized, respectively. A grain refinement layer was formed on the surface of different heat-treated specimens after ultrasonic-electric surface modification treatments. The average grain size on the top surface was refined into the submicrometer or nanometers scale. This is caused mainly by two aspects: one is the accumulation of initial tiny particles during deformation; the other is that the ferrite is smashed into pieces due to micro-fatigue damage. Moreover, it was found out the specimens after ultrasonic-electric surface modification treatment had shown the optimal surface properties and friction-wear properties.